Hungary : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors in Hungary using International Financial Reporting Standards (IFRS),International Standards on Auditing (ISA), and the relevant portions of European Union (EU) law (also known as the acquis communautaire) as benchmarks. It also draws on international experience and good practices in the field of accounting and audit regulation.